Posted by **Bud** on Saturday, March 3, 2012 at 5:40pm.

prove (cscx-secx/cscx+secx)=(cotx-1/cotx+1)

## Answer This Question

## Related Questions

- drwls - My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an ...
- Math - Im really struggling with these proving identities problems can somebody ...
- Pre Calculus - (secx)/(tanx)+(cscx)/(cotx)=secx+cscx Please help me verify this ...
- Precalculus/Trig - I can't seem to prove these trig identities and would really ...
- trig - express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is ...
- Trig - Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (x=theta BTW)
- Pre-Calculus - Find a numerical value of one trigonometric function of x if tanx...
- Precalculus - Complete the following identity secx-1/secx=? I have four multiple...
- trig proofs - cotx+tanx=secx+cscx
- Pre Calculus - (cotx)(cscx)+secx=(csc^2x)(secx) Please help to verify this ...

More Related Questions